Maternal exposure to UV filters: associations with maternal thyroid hormones, IGF-I/IGFBP3 and birth outcomes. Issue 2 (February 2018) - Krause, M; Frederiksen, H; Sundberg, K; Jørgensen, F S; Jensen, L N; Nørgaard, P; Jørgensen, C; Ertberg, P; Petersen, J H; Feldt-Rasmussen, U; Juul, A; Drzewiecki, K T; et al.
Abstract : Background: Several chemical UV filters/absorbers ('UV filters' hereafter) have endocrine-disrupting properties in vitro and in vivo . Exposure to these chemicals, especially during prenatal development, is of concern. Objectives: To examine maternal exposure to UV filters, associations with maternal thyroid hormone, with growth factor concentrations as well as to birth outcomes. Methods: Prospective study of 183 pregnant women with 2nd trimester serum and urine samples available. Maternal concentrations of the chemical UV filters benzophenone-1 (BP-1) and benzophenone-3 (BP-3) in urine and 4-hydroxy-benzophenone (4-HBP) in serum were measured by liquid chromatography–tandem mass spectrometry (LC–MS/MS). The relationships between 2nd trimester maternal concentrations of the three chemical UV filters and maternal serum concentrations of thyroid hormones and growth factors, as well as birth outcomes (weight, height, and head and abdominal circumferences) were examined. Results: Positive associations between maternal serum concentrations of 4-HBP and triiodothyronine (T3 ), thyroxine (T4 ), insulin-like growth factor I (IGF-I) and its binding protein IGFBP3 were observed in mothers carrying male fetuses. Male infants of mothers in the middle 4-HBP exposure group had statistically significantly lower weight and shorter head and abdominal circumferences at birth compared to the low exposure group. Conclusions: Widespread exposure of pregnant women to chemical UV filters and the possible impact on maternal thyroid hormones and growth factors, and on fetal growth, calls for further studies on possible long-term consequences of the exposure to UV filters on fetal development and children's health.